Limitations on the Age of Marriage and Its Legal Implications Perspective of Legal Expediency - HS, Fatimah; Pijoh, Feibe Engeline (Technium Social Sciences Journal, 2023)
The purpose of this study is to investigate the urgent reasons for changing the age limit for marriage law and to analyze the legal implications that emerged from the marriageable age limit in case of legal benefits. This research type uses normative juridical research. the source of data in this study is by examining primary data and enforcement of rules in practice. and how the form of legal safeguard is related to the problem to be studied. The outcomes of this study indicate that the revision of the marriage law has not fully succeeded in preventing the act of underage marriage. because although the law has been revised, the act of underage marriage continues due to a gap in the law itself with the dispensation of marriage. If this phenomenon is related to the theory developed by Jeremi Bentham, one could say that one of the law’s three goals, namely legal expediency, has not been achieved by the change of the marriage age limit.